✔ 最佳答案
Interesting, the point is the LCM of the denominator of the RHS of your 'Let' equation is (x²-1), not (x-1)(x+1)²,
which is differ from LHS.
So, you are using a wrong method.
(Instead, try the following)
Let x/[(x+1)(x²-1)]=(Bx+C)/(x²-1)+(Dx+E)/(x+1)²__________________x=(Bx+C)(x+1)+(Dx+E)(x-1)__________________x=(B+D)x²+(-B+C+D+E)x+(-Cx+E)By comparing the coefficientsB+D=0 --------(1)-B+C+D+E=1 ---(2)-C+E=0 -------(3)
So, D=-B, E=C, and 2B+2C=1
Suppose B=0, then C=1/2, D=0, E=1/2
x/[(x+1)(x²-1)]=(1/2)/(x²-1)+(1/2)/(x+1)²
Suppose C=0, then B=1/2, D=-1/2, E=0
x/[(x+1)(x²-1)]=(x/2)/(x²-1)-(x/2)/(x+1)²
Hope this can help you. (though it is not the best method)
2012-01-15 16:50:34 補充:
數無盡 學無涯 : But why can't it work
Ans : the denominator is wrong, so it can't work. for example
13/24 = A/4 + B/6
you can't find any integers that suitable for A and B and the LCM of 4 and 6 is not 24.